Integrating Dynamic Geometry Software into the 6E Instructional Model to Enhance Students’ Mathematical Communication Skills and Learning Autonomy - Dian Mustikaningsih; Yumiati Yumiati; Sudirman Sudirman; Camilo Andrés Rodríguez-Nieto (RANGE: Jurnal Pendidikan Matematika, 2026)
The integration of technology into mathematics instruction is increasingly acknowledged as a means to foster 21st-century competencies, particularly mathematical communication and independent learning. This study investigates the effects of the 6E instructional model combined with Dynamic Geometry Software (DGS) on these two aspects. A quasi-experimental design was conducted with tenth-grade students from a vocational school in Sukoharjo, Central Java. The sample included 35 students in the experimental group and 34 students in the control group, selected randomly. Mathematical communication was measured using essay-based pre- and post-tests, while learning autonomy was assessed through questionnaires administered before and after the intervention. Normality and homogeneity tests using Kolmogorov–Smirnov and Levene’s confirmed the assumptions for parametric analysis. Data were analyzed using the Independent Sample T-test. Results indicated that significance values for both mathematical communication and learning autonomy were below 0.05, showing statistically significant differences between groups. The experimental group achieved an average post-test score of 82.40, higher than the control group’s 74.24, indicating improved mathematical communication under the 6E model with DGS integration. Similarly, the experimental group’s average final questionnaire score of 105.11 exceeded the control group’s 90.38, reflecting greater learning autonomy. These findings demonstrate that embedding GeoGebra within the 6E instructional model substantially enhances students’ ability to articulate mathematical ideas and promotes independent learning. The study provides empirical support for technology-enhanced learning designs in mathematics education, highlighting their potential to strengthen key competencies and contribute to more effective instructional practices.